1969
DOI: 10.1083/jcb.42.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscope Radioautography as a Quantitative Tool in Enzyme Cytochemistry

Abstract: The distribution of diisopropylfluorophosphate (DFP)-sensitive enzyme sites at the neuromuscular junction was determined quantitatively by electron microscope radioautography after incubation of muscle fragments in DFP'H . Most of the sensitive sites were located in the subneural apparatus at a concentration of 90,000 sites per a' of cleft tissue or 12,000 sites per µ2 of postjunctional membrane surface area . A considerable concentration is also present in the teloglial cap . It has previously been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Based on this localization, we calculate 7,800 DFP sites and 2,500 2-PAM-reactivated sites//xm 2 of surface area of preand postjunctional membrane. This stacking density of DFP-binding sites per surface area of membrane (probably in the overlying sheets of basal lamina) is very similar to that in the diaphragm and sternomastoid muscles.KEY WORDS acetylcholinesterase extraocular muscle EM autoradiography track autoradiography neuromuscular junctions acetylcholine receptorIn several studies we have assessed the number of esterase sites both at the whole endplate (31, 32) and on the fine structural level (33,34,41). We found that in two different mouse muscles, the diaphragm and sternomastoid, there were about the same number of labeled sites per square micrometer of the folded postjunctional membrane (PJM).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Based on this localization, we calculate 7,800 DFP sites and 2,500 2-PAM-reactivated sites//xm 2 of surface area of preand postjunctional membrane. This stacking density of DFP-binding sites per surface area of membrane (probably in the overlying sheets of basal lamina) is very similar to that in the diaphragm and sternomastoid muscles.KEY WORDS acetylcholinesterase extraocular muscle EM autoradiography track autoradiography neuromuscular junctions acetylcholine receptorIn several studies we have assessed the number of esterase sites both at the whole endplate (31, 32) and on the fine structural level (33,34,41). We found that in two different mouse muscles, the diaphragm and sternomastoid, there were about the same number of labeled sites per square micrometer of the folded postjunctional membrane (PJM).…”
mentioning
confidence: 96%
“…In several studies we have assessed the number of esterase sites both at the whole endplate (31, 32) and on the fine structural level (33,34,41). We found that in two different mouse muscles, the diaphragm and sternomastoid, there were about the same number of labeled sites per square micrometer of the folded postjunctional membrane (PJM).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations